Berdampakkah Cemaran Dioksin Bagi Keadaan Gizi Dan Kesehatan? - Wiwin Efrizal (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2023)
Dioxins and related compounds can contaminate food and have an impact on human nutrition and health. The impact of dioxin contamination on nutrition and health is not widely known by consumers, because the effect lasts a long time after dioxin accumulates in fat tissue. Dioxins in the body can cause free radicals that can trigger oxidative stress, so that damage to several important cellular components can occur. Consumption of foods that contain antioxidants is an effort to minimize the negative effects caused by dioxin contamination in humans.